Lava flow rheology : a comparison of morphological and petrological methods - Chevrel, M. O.; Platz, Thomas; Hauber, Ernst; Baratoux, D.; Lavallée, Y.; Dingwell, D. B. (Freie Universität Berlin, 2013)
In planetary sciences, the emplacement of lava flows is commonly modelled using a single rheological parameter (apparent viscosity or apparent yield strength) calculated from morphological dimensions using Jeffreysʼ and Hulmeʼs equations. The rheological parameter is then typically further interpreted in terms of the nature and chemical composition of the lava (e.g., mafic or felsic). Without the possibility of direct sampling of the erupted material, the validity of this approach has remained largely untested. In modern volcanology, the complex rheological behaviour of lavas is measured and modelled as a function of chemical composition of the liquid phase, fractions of crystals and bubbles, temperature and strain rate. Here, we test the planetary approach using a terrestrial basaltic lava flow from the Western Volcanic Zone in Iceland. The geometric parameters required to employ Jeffreysʼ and Hulmeʼs equations are accurately estimated from high-resolution HRSC-AX Digital Elevation Models. Samples collected along the lava flow are used to constrain a detailed model of the transient rheology as a function of cooling, crystallisation, and compositional evolution of the residual melt during emplacement. We observe that the viscosity derived from the morphology corresponds to the value estimated when significant crystallisation inhibits viscous deformation, causing the flow to halt. As a consequence, the inferred viscosity is highly dependent on the details of the crystallisation sequence and crystal shapes, and as such, is neither uniquely nor simply related to the bulk chemical composition of the erupted material. This conclusion, drawn for a mafic lava flow where crystallisation is the primary process responsible for the increase of the viscosity during emplacement, should apply to most of martian, lunar, or mercurian volcanic landforms, which are dominated by basaltic compositions. However, it may not apply to felsic lavas where vitrification resulting from degassing and cooling may ultimately cause lava flows to halt.